Strabismus, visual acuity, and uncorrected refractive error in Portuguese children aged 6 to 11 years - Lança, Carla Costa (2014)
Introduction: Visual anomalies that affect school-age children represent an important public health problem. Data on the prevalence are lacking in Portugal but is needed for planning vision services. This study was conducted to determine the prevalence of strabismus, decreased visual acuity, and uncorrected refractive error in Portuguese children aged 6 to 11 years. Methods and materials: A cross-sectional study was carried out on a sample of 672 school-age children (7.69 ± 1.19 years). Children received an orthoptic assessment (visual acuity, ocular alignment, and ocular movements) and non-cycloplegic autorefraction. Results: After orthoptic assessment, 13.8% of children were considered abnormal (n = 93). Manifest strabismus was found in 4% of the children. Rates of esotropia (2.1%) were slightly higher than exotropia (1.8%). Strabismus rates were not statistically significant different per sex (p = 0.681) and grade (p = 0.228). Decreased visual acuity at distance was present in 11.3% of children. Visual acuity ≤20/66 (0.5 logMAR) was found in 1.3% of the children. We also found that 10.3% of children had an uncorrected refractive error. Conclusions: Strabismus affects a small proportion of the Portuguese school-age children. Decreased visual acuity and uncorrected refractive error affected a significant proportion of school-age children. New policies need to be developed to address this public health problem.